A Coordination Polymer based on Interconnection of Thioantimonate(III) and [Mn(terpy)]2+ Complexes: Synthesis, Crystal Structure, and Properties of {[(Mn(terpy))2Sb4S8]·0.5H2O}n. Issue 13 (8th April 2020) - Danker, Felix; Anderer, Carolin; Näther, Christian; Terraschke, Huayna; Bensch, Wolfgang
Abstract : Applying Schlippe's salt, Na3 SbS4 · 9H2 O, in the presence of the in‐situ formed [Mn(terpy)] 2+ complex (terpy = 2, 2':6', 2''‐terpyridine) the new compound {[(Mn(terpy))2 Sb4 S8 ]· 0.5H2 O} n (I ) could be obtained under solvothermal conditions. Interestingly, in the crystal structure the two unique Mn 2+ cations adopt different environments to form a MnN3 S3 octahedron and a MnN3 S2 trigonal pyramid. The trigonal pyramidal SbS3 3– anions share common edges yielding a Sb8 S8 ring. Covalent bonds between Mn 2+ and S 2– generate MnSb2 S3 and Mn2 Sb4 S6 heterocycles. The Sb8 S8 and Mn2 Sb4 S6 rings are condensed to form a chain. The MnN3 S3 octahedron and the MnN3 S2 polyhedron share a common S 2– anion and antiferromagnetic properties are observed mediated by superexchange interactions. {[(Mn(terpy))2 Sb4 S8 ]· 0.5H2 O} n shows luminescence in the blue‐green spectral range, assigned to combined contributions from Mn 2+ ions and from the organic ligand. Abstract :